Analisis Efektivitas Pengelolaan Dana Bantuan Operasional Sekolah (BOS) - Septhiningrum, Anggit Puteri; Sumtaky, Maxion; Zuhroh, Diana (Magister Akuntansi Universitas Pancasila, 2023)
This study aims to describe, analyze the accountability, transparency and effectiveness of management and transparency of the effectiveness of the management of school operational Assistance Fund (BOS) in Vocational/High School in Mojokerto. The principle of transparency and accountability is a measure that can’t be ignored from the weak strength of participation, which in this case includes, teachers, parents and school authorities. Accountability in the management of BOS funds refers to the right of parents, who are representatives of the community, to take part in being responsible for the implementation of the BOS fund assistance program. The researcher used a mixed research method, which is a method that unites quantitative and qualitative methods. The population in this study is the Principal, School Committee, and fund managers, who are the authorities in the fund manager BOS SMA/SMK in Mojokerto. While in technical analysis, this study uses multiple linear regression analysis. The research results show that accountability and transparency affect the effectiveness of BOS fund management